Keunggulan Wisata Kuliner Tahu di Korea - Meirina Diah Cahyani; Ummul Hasanah; Supriadianto Supriadianto (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
The article entitled “The Advantage of Tofu Culinary Tourism in Korea” is a qualitative descriptive research framework that analysed on the types of tofu in Korea based on its philosophical and tourism value. In Korea, the soy-based tofu is cooked and combined into some foods of high nutritional value, distinctive, unique, and modern. These foods are the main attraction in the world of Korean tourism that should be enjoyed. The data in this article were collected and analysed through literature study from various sources of information. The results of this study indicate that in principle tofu in Korea and Indonesia do not have significant differences, but in Korea, they can serve the tofu in the form of distinctive foods that characterizes their local wisdom.